Proceedings of the 1st International Conference on Innovation in Education (ICoIE 2018) 2019
DOI: 10.2991/icoie-18.2019.57
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Learning Methods on Students’ Critical Thinking: A Case at Social Studies

Abstract: The study aims to determine the effect of learning methods on social studies learning outcomes in terms of students' critical thinking. The study was conducted in SDN Talun Subdistrict, Cirebon Regency, by using experimental research on treatment by level 2 x 2 design. The results showed that (1) Social Studies learning outcomes between groups using the Problem Based Learning method were higher than students using the Problem Solving method, ( 2) There is an interaction effect between learning methods with cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Kesulitan belajar yang dialami siswa dikarenakan adanya ancaman, hambatan, dan gangguan yang dialaminya (Putra, 2018;Qomar, Marini, Sumantri, & Adiansha, 2019). Pada tingkat tertentu memang ada siswa yang mengatasi kesulitan belajarnya tanpa harus melibatkan orang lain.…”
Section: Pendahulanunclassified
“…Kesulitan belajar yang dialami siswa dikarenakan adanya ancaman, hambatan, dan gangguan yang dialaminya (Putra, 2018;Qomar, Marini, Sumantri, & Adiansha, 2019). Pada tingkat tertentu memang ada siswa yang mengatasi kesulitan belajarnya tanpa harus melibatkan orang lain.…”
Section: Pendahulanunclassified
“…Then, there is bound interaction between investigation, equity, and student cohesiveness aspects of social studies learning environment and students' critical thinking disposition (Meral & Tas, 2017). And another studies found that learning methods can influence students critical thinking skills on social studies learning outcomes (Qomar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Translating dialogue in the form of subtitles uses one of the translation procedures, namely cultural equivalents [4,5]. So, unconsciously translating activities is an act of transferring culture.…”
Section: Introductionmentioning
confidence: 99%